2015
DOI: 10.3354/esr00665
|View full text |Cite
|
Sign up to set email alerts
|

DNA from historical and trophy samples provides insights into white shark population origins and genetic diversity

Abstract: Characterizing genetic variation by retrospective genotyping of trophy or historical artifacts from endangered species is an important conservation tool. Loss of genetic diversity in top predators such as the white shark Carcharodon carcharias remains an issue, exacerbated in this species by declining, sometimes isolated philopatric populations. We successfully sequenced mitochondrial DNA (mtDNA) D-loop from osteodentine of contemporary South African white shark teeth (from 3 jaws), and from 34 to 129 yr old d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…However, there are currently a few examples of the use of aDNA for shark species. Gubili et al (2015) sequenced a small fragment (135-228 bp) of mtDNA (D-loop) from 34-to 129-yearold dried cartilage and skin samples from six Carcharodon carcharias individuals and found greater genetic diversity (number of haplotypes and nucleotide and haplotype diversity) in the historical samples than in contemporary samples found in the Mediterranean Sea. Moreover, Li et al (2015) used the complete mitochondrial genome of aDNA to infer the phylogeny and gene flow of endangered river sharks (Glyphis spp., Carcharhinidae).…”
Section: Genetic Monitoring By Sampling In Temporal Series To Assess mentioning
confidence: 99%
“…However, there are currently a few examples of the use of aDNA for shark species. Gubili et al (2015) sequenced a small fragment (135-228 bp) of mtDNA (D-loop) from 34-to 129-yearold dried cartilage and skin samples from six Carcharodon carcharias individuals and found greater genetic diversity (number of haplotypes and nucleotide and haplotype diversity) in the historical samples than in contemporary samples found in the Mediterranean Sea. Moreover, Li et al (2015) used the complete mitochondrial genome of aDNA to infer the phylogeny and gene flow of endangered river sharks (Glyphis spp., Carcharhinidae).…”
Section: Genetic Monitoring By Sampling In Temporal Series To Assess mentioning
confidence: 99%
“…They were able to amplify and sequence a large (700 bp) mitochondrial DNA segment from 44% (15) of the historical samples. Recently, Gubili et al (2015) extracted DNA from 34-to 129-year-old samples of fins and cartilage from six white sharks for subsequent successful analysis of small (135-228 bp) mtDNA sequences. Thus, both studies were primarily focused on demonstrating the applicability of archived shark samples for PCR amplification of mtDNA segments.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made in the past to resolve the phylogenetic relationships of the Mediterranean GWS population using mitochondrial DNA (mtDNA) sequences (Gubili et al, , ). Using up to five specimens from the Mediterranean, Gubili et al (, ) concluded that the population is more closely related to populations in the Pacific Ocean (Australia, New Zealand and North‐eastern Pacific) than to those from the western Indian Ocean (South Africa) and north‐western Atlantic Ocean (Florida).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made in the past to resolve the phylogenetic relationships of the Mediterranean GWS population using mitochondrial DNA (mtDNA) sequences (Gubili et al, , ). Using up to five specimens from the Mediterranean, Gubili et al (, ) concluded that the population is more closely related to populations in the Pacific Ocean (Australia, New Zealand and North‐eastern Pacific) than to those from the western Indian Ocean (South Africa) and north‐western Atlantic Ocean (Florida). Based on a nucleotide substitution rate between the two major lineages (North‐eastern Pacific vs. North‐West Atlantic and Eastern Indian) calibrated by the formation of the Isthmus of Panama (3.5 Ma) and the Sunda‐Sahul Shelves (5 Ma), respectively, Gubili et al () suggested that Mediterranean GWS are descendants of a few disoriented individuals who immigrated from Australia/New Zealand during the Pleistocene (348–565 ka) by an antipodean route along the western coast of Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation